Does board gender diversity enhance ESG performance? Empirical evidence from Indonesia - Pernamasari, Rieke (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2025)
This study explores the impact of board gender diversity (BGD) on sustainability performance, measured Environmental, Social, and Governance (ESG) disclosure scores, in the Indonesian context. A fixed-effect panel data regression was applied to 405 firm-year observations from 81 companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The results show that BGD positively influences overall ESG performance, with a significant effect on governance performance. However, no significant impact was found on the environmental and social dimensions. These findings suggest that female representation on corporate boards may strengthen governance practices, though its influence on environmental and social initiatives remains limited. This research contributes to the literature on gender diversity and ESG by offering empirical evidence from an emerging market, providing insights for regulators and stakeholders to promote inclusive leadership and sustainable business practices.